Swimming Using a Unidirectionally Rotating, Single Stopping Flagellum in the Alpha Proteobacterium Rhodobacter sphaeroides - Armitage, Judith P. (Frontiers in Microbiology, 2022)
Rhodobacter sphaeroides has 2 flagellar operons, one, Fla2, encoding a polar tuft that is not expressed under laboratory conditions and a second, Fla1, encoding a single randomly positioned flagellum. This single flagellum, unlike the flagella of other species studied' only rotates in a counterclockwise direction. Long periods of smooth swimming are punctuated by short stops, caused by the binding of one of 3 competing CheY homologues to the motor. During a stop the motor is locked, not freely rotating.and the flagellar filament changes conformation to a short wavelength, large amplitude structure, reforming into a driving helix when the motor restarts. The cell has been reoriented during the brief stop and the next period of smooth swimming is a new direction..